2016
DOI: 10.1007/s12273-016-0296-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the unsteady flow characteristics of human body thermal plume

Abstract: Human thermal plume is quite important to the study of airflow organization in the indoor environment, especially in the micro-environment research such as personalized ventilation, infectious disease transmission through air, etc. In order to investigate the unsteady fluctuation of the thermal plume around human body, a series of transient numerical simulations are conducted in this study. Numerical simulation based on 9.7 million grids and 0.02 s time step is performed to obtain the detail quantitative data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The line y = 1.35 is quite uniform due to the boundary layer effect, which is rather stable on the surface of the manikin. For the frequency, it is observed that the thermal plume oscillates with a low frequency and the dominant frequency is around 0.1 Hz which matches the result in Liu et al (2016).…”
Section: Natural Convection Regionsupporting
confidence: 82%
See 3 more Smart Citations
“…The line y = 1.35 is quite uniform due to the boundary layer effect, which is rather stable on the surface of the manikin. For the frequency, it is observed that the thermal plume oscillates with a low frequency and the dominant frequency is around 0.1 Hz which matches the result in Liu et al (2016).…”
Section: Natural Convection Regionsupporting
confidence: 82%
“…(5) and further obtain the initial condition for the unsteady simulation. Liu et al (2016) found that the dominant frequency of thermal plume from human body is less than 1 Hz. Thus, the physical unsteady time step is set as 0.04 s. To prevent the initial flow conditions, the first 400 time steps were removed from the results.…”
Section: Single-row Aircraft Cabin Simulationmentioning
confidence: 98%
See 2 more Smart Citations
“…Fig. 5(d) shows another scenario related to the thermal plume generated by the target person, which has been proven to be important in the near-body airflow field and contaminant transport (Liu et al 2016;Yan et al 2017). When the exhaled air penetrates the lower zone of the thermal plume boundary layer, the contaminants may move upward with the vertical airflow driven by the thermal plume and enter the breathing zone.…”
Section: Development Of the Methodsmentioning
confidence: 99%